Getting better at sensemaking - Woodside, Arch G. (Advances in business marketing and purchasing, 2000)
This work's 16 contributions fill the mind with knowledge, skills, and insights useful for improving the executive's ability to do what needs to be done: scan environments better to find the weak signals on breakthrough technologies; understand shifts in customers' attitudes and behaviors; observe changes in behaviors of suppliers, governments, and other stakeholder groups; frame problems/opportunities better by deepening understanding on how we go about making sense of what is happening and can be made to happen; decide better by gaining deep knowledge on how decisions are actually made and can be improved (e.g., via systems thinking and simulating system operations to uncover powerful levers previously unrecognized); and, do better by applying new tools to learn what is really happening when planned strategies are converted into realized strategies.